Lauryn Smith: capstone - Smith. Lauryn, artist (Colorado State University. Libraries, 2025)
The artist's statement: My work as a digital artist has focused on the body's connection to the world around us. The body is always changing, and the life stored in it can be profoundly impactful. We use the body to draw conclusions about the state of the world and ourselves. Through 3D art and animation, I explore the idea of the body in relation to the outside world, focusing on the parts of ourselves that we cannot ignore. While my main focus is digital art, it is important to put emphasis on the fact that I am a multi-media artist. I find that by practicing different mediums, I am able to translate the skills I gain through sculpting and painting into the digital world. I feel that it is important not to become too separated from the physical world, and I want that to reflect in the work I create, especially with the circus on the human body and its experience.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art